2022
DOI: 10.1152/ajpgi.00299.2021
|View full text |Cite
|
Sign up to set email alerts
|

Role of excretion in manganese homeostasis and neurotoxicity: a historical perspective

Abstract: The essential metal manganese (Mn) induces incurable neurotoxicity at elevated levels that manifests as parkinsonism in adults and fine motor and executive function deficits in children. Studies on Mn neurotoxicity have largely focused on the role and mechanisms of disease induced by elevated Mn exposure from occupational or environmental sources. In contrast, the critical role of excretion in regulating Mn homeostasis and neurotoxicity has received less attention although (1) studies on Mn excretion date back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 95 publications
1
18
0
Order By: Relevance
“…3 ), being unable to differentiate between highly and moderately exposed groups (medians 9.16 µg/L vs. 9.18 µg/L, p = 0.865), even after adjusting for potential confounders. This is in agreement with previous studies reporting that Mn levels are tightly regulated in this matrix, with excess being quickly eliminated by the liver and excreted in bile and urine (Gurol et al, 2022 ). The correlation analysis also confirmed that whole blood cannot be used as biomarker of environmental exposure to Mn with epidemiological purposes, as it did not show significant correlations with any of the Mn fractions analysed in PM, nor with other biomarkers, nor with distance to the source.…”
Section: Discussionsupporting
confidence: 93%
“…3 ), being unable to differentiate between highly and moderately exposed groups (medians 9.16 µg/L vs. 9.18 µg/L, p = 0.865), even after adjusting for potential confounders. This is in agreement with previous studies reporting that Mn levels are tightly regulated in this matrix, with excess being quickly eliminated by the liver and excreted in bile and urine (Gurol et al, 2022 ). The correlation analysis also confirmed that whole blood cannot be used as biomarker of environmental exposure to Mn with epidemiological purposes, as it did not show significant correlations with any of the Mn fractions analysed in PM, nor with other biomarkers, nor with distance to the source.…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that the expression of influx manganese transporters was each decreased to ~60% in these mutant cells (Fig. 6C, SLC11A2, SLC39A8 and SCL39A14) (46, 47). These transporter phenotypes were different from the phenotypes in SLC30A10 Δ cells (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Note that, in addition to the basal ganglia regions, we included the thalamus in these assays because it expresses SLC30A10 30 and receives the basal ganglia output 23,24 , and we conducted the experiment at PND 21 because previous studies show that the effect of oral Mn exposure on brain Mn levels is highest in early postnatal life (i.e. around PND 21) before Mn excretory capacity of rodents is fully developed 22,39-41 . Importantly, Mn treatment also increased blood Mn levels at PND 21, but there was no difference between pan-neuronal/glial knockouts and littermate controls ( Fig.1C ), implying that Mn level increases observed in the basal ganglia and thalamus of the pan-neuronal/glial knockouts were independent of the excretory function of SLC30A10.…”
Section: Resultsmentioning
confidence: 99%
“…Mn-induced parkinsonism is also recognized in individuals with compromised hepatic excretory function (e.g. due to cirrhosis), even in the absence of elevated Mn exposure, because Mn is primarily excreted by the liver 22 . More recently, epidemiological studies have suggested that environmental Mn exposure (e.g.…”
Section: Introductionmentioning
confidence: 99%